What drives capacity to innovate? Insights from women and men small-scale farmers in Africa, Asia, and Latin America - Badstue, Lone B.; López, Diana E.; Umantseva, Anja; Williams, George; Elias, Marlène; Farnworth, Cathy Rozel; Rietveld, Anne M.; Njuguna-Mungai, Esther; Luis, Joyce S.; Najjar, Dina; Kandiwa, Vongai (2018)
What are key characteristics of rural innovators? How are their experiences similar for women and men, and how are they different? To examine these questions, we draw on individual interviews with 336 rural women and men known in their communities for trying out new things in agriculture. The data form part of 84 GENNOVATE community case studies from 19 countries. Building on study participants’ own reflections and experiences with innovation in their agricultural livelihoods, we combine variable-oriented analysis and analysis of specific individuals’ lived experience. Results indicate that factors related to personality and agency are what most drive women’s and men’s capacity to innovate. Access to resources is not a prerequisite but rather an important enabling aspect. Different types of women have great potential for local innovation, but structural inequalities make men better positioned to access resources and leverage support. Men’s support is important when women challenge the status quo.